2018
DOI: 10.1039/c8qo00653a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diels–Alder cycloadditions of benzofulvene-based 2,4-dienals via trienamine activation

Abstract: A new type of 2,4-dienal featuring a benzofulvene skeleton is utilised in asymmetric Diels–Alder cycloadditions with 3-olefinic oxindoles via trienamine catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Herein, benzofulvenes 15 as 2,4‐dienals were shown to react with dienophile 16 via trienamine intermediates. Through this strategy, a library of polyhydrofluorenes 17 was generated with high level of regio‐ and enantioselectivities in moderate to high yields (Scheme ) …”
Section: Dienals and Dienones In Trienamine Catalysismentioning
confidence: 99%
“…Herein, benzofulvenes 15 as 2,4‐dienals were shown to react with dienophile 16 via trienamine intermediates. Through this strategy, a library of polyhydrofluorenes 17 was generated with high level of regio‐ and enantioselectivities in moderate to high yields (Scheme ) …”
Section: Dienals and Dienones In Trienamine Catalysismentioning
confidence: 99%
“…Benzofulvenes, a kind of synthon having semi-aromatic characteristics, have been mainly employed in the synthesis of polymeric compounds and transition-metal-complexes. 11 In comparison, the utilization of these synthons to construct small molecules was rarely reported, particularly in a catalytic asymmetric manner, 12 which may be ascribed to the low activity of the diene in the benzofulvene. In 2016, Jørgensen introduced an electron-withdrawing group at the 3-position of the benzofulvene to enhance the reactivity of the exocyclic double bond, which served as a 2π-component to react with 2,4-dienals or dimethyl bromomalonate in the presence of chiral catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified a number of benzofulvene-containing natural products with remarkable biological and pharmaceutical potential . In addition, functionalized benzofulvenes are also versatile building blocks widely used among the synthetic community …”
mentioning
confidence: 99%